Taking Their Word : Literature and the Signs of Central America - Arias, Arturo (Book collections on Project MUSE., 2007)
In Taking Their Word, Arias complicates notions of the cultural production of Central America. Arias demonstrates that Central America and its literature are marked by an indigenousness that has never before been fully theorized or critically grasped. With this groundbreaking work, Arias establishes the importance of Central American literature and provides a frame for future studies of the region's culture.